Young boy dressed as a clown for Halloween - Unknown:::Creator::::::::::::
Photograph shows a little boy dressed up in a clown costume, probably for Halloween. He has also had his face painted to look like a clown and is standing next to a basket with boxes of play food, such as chocolate milk, popcorn, and cherry pie. There is another child in the background who is also in costume. They are probably at the YWCA's day care center.